This Poem Doesn't Rhyme - "Benson, Gerard" (Penguin Random House Children's: UK, [S.l.], 1994)
An award-winning collection from Gerard Benson, creator of Poems on the Underground. James Berry and Wendy Cope appear alongside Milton and Shakespeare amongst others to make a wonderfully diverse, fun and exciting collection of verse that shows that poetry doesn't have to rhyme
Keywords: Poetry